TRIM28 mediates Mettl5 ubiquitination to promotes Th2 polarization - Miao, Beiping; Mo, Lihua; Miao, Shihan; Zhang, Xiwen; Zheng, Haoyue; Dong, Yixuan; Xie, Bailing; Zhang, Yuanyi; Liao, Yun; Liu, Yu; Tang, Ping; Yang, Pingchang (Frontiers in Immunology, 2025)
BackgroundTh2 polarization is the primary characteristic of airway allergy (AA) and many other immune disorders. Further elucidation of its mechanism is necessary. The immune cells of patients with immune diseases have been found to have abnormal epigenetic status. This research intends to examine the role of methyltransferase-like 5 (Mettl5) in regulating homeostasis in CD4+ T cells.MethodsAn AA mouse model was established with dust mite extracts as a specific antigen. The epigenetic marks in the Gata3 gene of CD4+ T cells were evaluated using chromatin immunoprecipitation assay and cross-enzyme-linked immunosorbent assay.ResultsSpontaneous airway Th2 polarization was observed in mice carrying Mettl5-deficient CD4+ T cells. The quantity of Mettl5 was decreased in airway CD4+ T cells of AA mice, which was negatively correlated with the AA response. Hyperubiquitination was detected in Mettl5 in airway CD4+ T cells of AA mice, which was negatively correlated with hypomethylation status at the Gata3 promoter and the high transcription activity of the Gata3 gene. The elevated quantity of TRIM28 was detected in airway CD4+ T cells of AA mice. The presence of TRIM28 induced Mettle protein ubiquitination and degradation in CD4+ T cells. Inhibition of TRIM28 reconciled the Mettl5 activity and Gata3 gene transcription in airway CD4+ T cells of AA mice, and attenuated AA.ConclusionsLow Mettl5 levels in airway CD4+ T cells resulted in Th2 polarization. Inhibition of TRIM28 restored the levels of Mettl5 in airway CD4+ T cells, and suppressed experimental AA.